Genome-wide characterization of major latex protein gene family in peanut and expression analyses under drought and waterlogging stress - Li, Jie; Zeng, Ruier; Huang, Zijun; Gao, Hengkuan; Liu, Shiyuan; Gao, Yu; Yao, Suzhe; Wang, Ying; Zhang, Hui; Zhang, Lei; Chen, Tingting (Frontiers in Plant Science, 2023)
Peanut is an important oilseed crop around the world which provides vegetable oil, protein and vitamins for humans. Major latex-like proteins (MLPs) play important roles in plant growth and development, as well as responses to biotic and abiotic stress. However, their biological function in peanut is still unclear. In this study, a genome-wide identification of MLP genes in cultivated peanut and two diploid ancestor species was analyzed to determine their molecular evolutionary characteristics and the expression profile under drought and waterlogging stress conditions. Firstly, a total of 135 MLP genes were identified from the genome of tetraploid peanut (Arachis hypogaea) and two diploid species Arachis. duranensis and Arachis. ipaensis. Then, phylogenetic analysis revealed that MLP proteins were divided into five different evolutionary groups. These genes were distributed unevenly at the ends of chromosomes 3, 5, 7, 8, 9 and 10 in three Arachis species. The evolution of MLP gene family in peanut was conserved and led by tandem and segmental duplication. The prediction analysis of cis-acting elements showed that the promoter region of peanut MLP genes contained different proportions of transcription factors, plant hormones-responsive elements and so on. The expression pattern analysis showed that they were differentially expressed under waterlogging and drought stress. These results of this study provide a foundation for further research on the function of the important MLP genes in peanut.